Madhumeha(Diabetes Mellitus): An AyurvedaReview - Walmiki, Parashuram; Kumar, Pradeep; Chowdhury, Nur Mohammad Iqbal; Godatwar, PawanKumar (International Research Journal of Ayurveda & Yoga, 2024)
Diabetes Mellitus (DM), usually known as diabetes, is a group of metabolic disorders characterized by high blood sugar levels over a prolonged period.Globally, an estimated 422 million adults are living with diabetes, according to the latest 2016 data from the World Health Organization(WHO)1.India has being estimated with fastest growing population of diabetics. It is a metabolic disorder may result in deficiency or dysfunction of the insulin production. The preventive measures in Ayurveda can prevent be the disease. The main causative factor is said to be sedentary lifestyle and food habits. In Ayurveda it is described in prameha, which can be managed conservatively with exercise, diet and internal medication.